2007
DOI: 10.1080/00207450701537076
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Training for Prehospital Providers

Abstract: The amount of training in the past year reported for CBRN events varied greatly, with almost a quarter recalling no education. Drills and lectures were the most used and preferred formats for disaster training. Prehospital providers felt least prepared for a radiological;/nuclear event. Future studies should focus on the consistency and quality of education provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…An additional 19% reported only one to five hours of training in the preceding year in MCEs or CBRN. 9 A study by Reilly et al 10 also demonstrated a persistent lack of adequate training in disaster and terrorism response for EMS providers. They state that "responder training .…”
Section: Training and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 19% reported only one to five hours of training in the preceding year in MCEs or CBRN. 9 A study by Reilly et al 10 also demonstrated a persistent lack of adequate training in disaster and terrorism response for EMS providers. They state that "responder training .…”
Section: Training and Educationmentioning
confidence: 99%
“…10,11 The lack of standardized training and well-defined core competencies in disaster management makes it difficult to assess preparedness of the EMS community. 9 Emergency medical services medical directors have been tasked with establishing and enhancing competency-based core curricula in emergency preparedness and response for EMS providers and ensuring that adequate training is implemented.…”
Section: Training and Educationmentioning
confidence: 99%
“…Surveys taken in the United States that asked paramedics about perceived preparedness for terrorist events or events from weapons of mass destruction showed similar results. [15][16][17] In Canada, at the federal level, there is infrastructure for planning and training; however, the "trickle down" to the local level has not been substantial. The Canadian Emergency Management College trains teams in combined CBRN response, but this is a slow process.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Three surveys published in 2007 evaluated the self-reported training of EMS providers for CBRN-type events in the United States and found that the rates of training were worryingly low. [15][16][17] We could not locate an equivalent survey of Canadian EMS providers, and are aware of only a small number of specific CBRN teams in selected locations. We have previously studied Canadian hospital readiness for CBRN events, 2 but no study describes the prehospital component.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,7,8 However, there are frequent reports of a lack of preparedness and EMS provider training for chemical mass-casualty situations. [9][10][11][12][13] The level of Finnish EMS preparedness for chemical mass-casualty situations is unknown. The aim of this study was to assess the current level of preparedness of the Finnish EMS for responding to chemical mass-casualty situations in Finland.…”
Section: Introductionmentioning
confidence: 99%